THE SPECIFICITY OF DEVELOPMENT AND THE FORMATION OF THE PECULIARITIES OF THE RUSSIAN ANIMATIONAL INDUSTRY IN THE CONTEXT OF THE CONCEPTION OF CHILDHOOD PART 2 / СПЕЦИФИКА РАЗВИТИЯ И ФОРМИРОВАНИЕ ОСОБЕННОСТЕЙ ОТЕЧЕСТВЕННОЙ АНИМАЦИОННОЙ ИНДУСТРИИ В КОНТЕКСТЕ КОНЦЕПЦИИ ДЕТСТВА ЧАСТЬ 2 - KRIVULYA NATALIA G. / КРИВУЛЯ НАТАЛЬЯ ГЕННАДЬЕВНА (Наука телевидения)
The article examines the specificity and the peculiarities of Russian animation. During the course of the entire period of its development it was formed as the domain of the screen industry manufacturing articles for children. The directedness on the children’s audience was set in Russian animated films in the early 1930s in line with the formation of children’s cinematography. With the establishment of the “Soyuzmultfilm” studio in 1936 the release of animated films became prioritized for this field. This directedness was preserved in the animated film industry until the mid-1980s. With the beginning of the Perestroika there was a weakening of this tendency, the vectors of development of animation changed. Already beginning with the mid-1950s the animators attempted to broaden the narrow boundaries of animation and actively to create films for audiences of other age groups. Directedness towards an adult auditorium became prioritized for the Russian animated film industry in the 1990s and the 2000s. During the final decade of the 20th century serious transformations in the animated industry. Despite the appearance of numerous independent animation studios, they found themselves on the brink of total destruction. During those years the systems of children’s film rental and children’s television was liquidated. Release of films and programs for children was almost entirely terminated. Changes in the field of animation began to take shape in the middle of the first decade of the 21st century, when initiatives started to be undertaken from the side of the government directed at the revival of this branch. The first serious changes began to be observed towards the mid-2010s. The revival of the animated film industry began, but only as a field of children’s cinematography. In many ways this happened as the result of state polity directed towards the development of the children’s segment of the audiovisual industry.